Flow, Stagnation, and Renewal: Understanding the Symbolic Dimensions of Water in Anuradha Roy’s ‘An Atlas of Impossible Longing’ - Revathy Janarthanan; Murugavel Sundaramoorthy; Aravind Banumathi Rajamanickam; Pitchaimani Amudha (Forum for Linguistic Studies, 2024)
Water is one of nature's gifts to the earth, carrying a multitude of meanings and interpretations based on its context. Water in literature is studied from a variety of theoretical perspectives due to its rich symbolism and different narrative roles. This paper aims to explore Indian writer Anuradha Roy’s novel, "An Atlas of Impossible Longing," through Gaston Bachelad’s water symbolism theory and investigates how numerous types of water bodies, including rivers, ponds, and rain, each with its own meanings and thematic importance, with the river playing a central part in the novel. This study explores the symbolism of water through three key themes: "Flow and Transformation," "Stagnation and Reflection," and "Renewal and Destruction." It examines how water functions as both a healing and destructive force in human life. Using a qualitative approach, the study combines textual analysis with theoretical interpretation based on Gaston Bachelard’s symbolism theory from Water and Dreams: An Essay on the Imagination of Matter. Through a close reading of the novel, it highlights how water serves as a metaphorical device, reflecting characters’ emotional states, personal growth, and existential challenges. This research stands out by providing a comprehensive analysis of how Anuradha Roy integrates water symbolism in contemporary Indian Literature through her narrative structure and highlights its multidimensional role in the story. The novelty lies in its comparative analysis of Roy’s water imagery with broader literary traditions, creating new insights into how water symbolism functions both as an ecological signifier and a transformative metaphor in the human experience.